Riqueza e composição, lacunas de conhecimento e conservação dos crocodilianos do estado do Tocantins, ecótono Amazônia- Cerrado, Brasil - Dornas, Tulio (2021)
Six species of alligatorids occur in Brazil, but only three have been recorded from the state of Tocantins: Melanosuchus niger, Caiman crocodilus and Paleosuchus palpebrosus. The objectives of this study are to present a synthesis of the knowledge of crocodilians of Tocantins, describing geographical distribution of species, and some aspects of conservation. The exhaustive compilation of records in the literature, herpetological collections and surveys carried out in the field by the authors confirmed the occurrence also of Paleosuchus trigonatus. Although a specimen of C. latirostris was reported from Tocantins, it was possibly erroneously labeled. To investigate knowledge gaps, we divided the state into 95 grid cells of 300,000 hectares. Only 55% of Tocantins State has received some sampling for crocodilians, regardless of the method of registration. Only 12% of the state has been sampled considering any level of documentation and only 1.6% of the state had collection and deposit of specimens in a scientific collection. Only P. trigonatus does not have records within full-protection conservation areas and/or indigenous lands in Tocantins State. Hunting pressure and dams on the Tocantins River may lead to a decrease in the density of M. niger. A systematic program for monitoring and surveying for caimans is suggested to consolidate the knowledge of this animal group in Tocantins State.